Dynamic Network Analysis of Functional Connectivity in Dementia: Unraveling Temporal Patterns and Therapeutic Implications - Abdulyekeen, T. Adebisi; Al-Musibahu, AbdulRahim (Journal of Neurological Research And Therapy, 2024)
Exploring the dynamic dimension of functional connectivity in dementia, this article departs from traditional static studies to capture the ever-changing brain networks. Investigating temporal connectivity patterns yields valuable insights into disease progression, individualized treatment, and early intervention. Additionally, the concept of cognitive reserve, therapeutic interventions, and machine learning integration are pivotal in revolutionizing dementia research and care.
Keywords: Alzheimer’s Disease (AD); Complex network theory; Electroencephalogram (EEG); Graph theory; Functional connectivity